Biochemical, Microbial and Sensory Changes of Bombay duck (Harpodon nehereus) Fish Fingers during Chilled Storage - Jeyakumari, A.; Murthy, L. N.; Vishnuvinayagam, S. (Fishery Technology, 2017)
Bombay duck (Harpodon nehereus) is one of the important fishery species along Gujarat and Maharashtra coasts. Due to a very high moisture content (90%), it is unsuitable to use either in fresh or in frozen form and almost entire catch is consumed in sundried form. This study is aimed to explore the possibilities of better utilization of this species by development of battered and breaded fish fingers. Fish fingers were prepared from Bombay duck fillet and their qualities were evaluated under chilled storage up to 21 days. Fish fingers had 52.43% moisture, 12.25% protein, 10.17% fat, 2.03% ash and 23.12% carbohydrate. Results showed increasing trend in pH, TVB-N, FFA, PV and TBA values (p<0.05) during storage. Microbiological analysis revealed that total plate count of fish fingers was within the acceptable limit (1.29 x 104 cfu g-1 on 21st day) throughout the storage period. Sensory evaluation showed decrease in overall acceptability of fish finger during chilled storage. Results indicate that fish fingers from Bombay duck can be stored for 15 days in 4Â°C without change in sensory quality.